USE OF ENERGY-SAVING TECHNOLOGIES IN HIGHER EDUCATION INSTITUTIONS - MATIUKH, Serhii; SKYBA, Mykola; SYNYUK, Oleh; HORIASHCHENKO, Serhiy (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article examines the requirements for the creation of an autonomous university, considers alternative measures to solve energy saving problems, shows the effectiveness and necessity of conducting an energy audit of the institution, indicates the actions performed by Khmelnytskyi National University in the framework of energy saving. The methodology for evaluating the effectiveness of measures is similar to the calculation of current energy consumption and energy consumption for the previous representative period. The difference is that when evaluating energy-saving measures, it is necessary to predict how the situation will change after their implementation. This entails a change in many coefficients, such as the rate of energy consumption, the power utilization coefficient, the duration of equipment operation during the year.To save energy, Khmelnytskyi National University built its own boiler house with a capacity of 3,900 kW, which made it possible to disconnect several buildings from the city-wide heat supply network. Solar power plants were put into operation, solar panels were placed on the roofs of the buildings of the educational institution, educational and production bases, sports complexThe implementation of the latest technologies for the production and consumption of energy resources, as well as technologies involving the use of alternative energy sources, is possible on the basis of a previously conducted comprehensive energy audit. The feasibility of building an autonomous heating system, which made it possible to disconnect the main buildings from the city-wide heat supply network, has been proven. Taking measures to insulate walls, replace the water supply system, and use heating points increases the energy efficiency of resource use. In addition, the introduction of alternative energy systems, the creation of own solar power plants and modern control systems for them allows you to optimize lighting costs per hectare, reduce costs for electricity needs, and even make money from sales using the “green tariff”.In this way, any higher educational institution can organize and conduct its own measures to increase the energy-efficient consumption of energy resources, conduct information campaigns, involving students and teachers. This will not only improve the energy situation at the university, but will also help save energy at home.
Keywords: save energy; university; energy efficiency; solar power plants